“It spreads like wildfire”: mothers’ gatherings for vaccine acceptance - de Acosta, Diego; Moore, Temple; Alam, Fariha; Hoffman, Sarah J.; Keaveney, Megan; Mann, Erin; Dawson-Hahn, Elizabeth (Frontiers in Public Health, 2024)
This case study describes the design, implementation, and evaluation of an initiative to increase COVID-19 vaccine confidence and uptake among refugee and immigrant women in Clarkston, Georgia. Applying the principles and practices of human-centered design, Mothers x Mothers was cocreated by Refugee Women's Network and IDEO.org as a series of gatherings for refugee and immigrant mothers to discuss health issues, beginning with the COVID-19 vaccine. The gatherings included both vaccinated and unvaccinated mothers and used a peer support model, with facilitation focused on creating a trusting environment and supporting mothers to make their own health decisions. The facilitators for Mothers x Mothers gatherings were community health workers (CHWs) recruited and trained by Refugee Women's Network. Notably, these CHWs were active in every phase of the initiative, from design to implementation to evaluation, and the CHWs' professional development was specifically included among the initiative's goals. These elements and others contributed to an effective public health intervention for community members who, for a variety of reasons, did not get sufficient or appropriate COVID-19 vaccine information through other channels. Over the course of 8 Mothers x Mothers gatherings with 7 distinct linguistic/ethnic groups, 75% of the unvaccinated participants decided to get the COVID-19 vaccine and secured a vaccine referral. the National Association of City and County Health Officials (NACCHO), which is also funded by the CDC (award number NU38OT000306).We wish to thank Ridhi Arun and Claudia Sosa Lazo of IDEO.org for their review of this case study, and we express our gratitude to the IDEO.org teams who were involved in the design of Mothers x Mothers.